Effect of silvicultural treatments on buluh madu (Gigantochloa albociliata (Munro) Kurz) for shoot production - Mohamed, Johar (2012)
Bamboo recources in Malaysia are limited and usually acquired from forest wildly and also small scale bamboo plantation. It has high potential and demand in the local market and worldwide. Most of the bamboo shoots in the local market are still being imported from other countries, especially China, Taiwan and Thailand. Therefore, this study was carried out to determine the best Silviculture treatment (planting technique, fertilizer regime, harvesting method) and their interaction for commercial shoot production. 480 seedlings were arranged using Split-Split-Plot design while the data was analyzed using SPSS 12.0. The parameters were number of culm, heigh of culm, number of shoot, height of shoot and weight of shoot. There are significant difference p at ≤0.05 level for fertilizer regime; which chicken dung give highest of all parameters compared to NPK. Harvesting method showed significant difference at p ≤0.05 with 51%-75 % harvesting method for number of culm and height of clump, but no significant for number of shoot, height of shoot and weight of shoot. Planting technique also showed significant difference at p ≤0.05 level for height of clump but no significant different for other parameter. However, there was significant difference at p ≤0.05 level for interaction between harvesting method and planting technique for number of culm and height of clump. The significant difference also showed for interaction between fertilizer regime and planting technique for shoots parameters. Rainfall have high effect to bamboo shoot production.Commercial bamboo plantation for shoot production need a good irrigation system for water supply, using chicken dung (organic fertilizer), control harvesting method with range 51 % - 75 % harvesting for sustainable yield and maintained residues.